Analisis Hubungan Sektor Ekonomi Basis dengan Penyerapan Tenaga Kerja di Kabupaten Sidoarjo - Eka Aprilia N. Sagita; Niniek Imaningsih; Riko Setya Wijaya (Syntax Corporation Indonesia, 2024)
This research aims to examine the relationship between the Basic Economic Sector and Labor Absorption for the 2018-2022 period. This research uses secondary data with a quantitative approach. The population in this study is data from the Annual Gross Regional Domestic Product Report for East Java and Sidoarjo Regency and data on Labor Absorption of Sidoarjo Regency. The sample used is annual Gross Regional Domestic Product data based on constant prices, basic sectors and labor absorption using a sample of the last 5 years, namely 2018 to 2022. The analysis method used in this research is the LQ method and data regression analysis method using SPSS software in carrying out data processing. The results of this research show that the Sidoarjo Regency Base Sector analysis in 2018-2022 produced 3 superior sectors, namely the Processing Industry Sector, the Electricity and Gas Procurement Sector, and the Transportation and Warehousing Sector. Meanwhile, the simultaneous results of the Base Sector variable have a significant effect on Labor Absorption. Partially, the Base Sector has a positive and significant effect on Labor Absorption. The Base Sector variable is able to explain variations in the Cooperative Capital variable of 98.4% and 1.6% is influenced by other factors not included in the research variables